2014
DOI: 10.4018/ijtem.2014010102
|View full text |Cite
|
Sign up to set email alerts
|

Fostering Students' ‘Use My Own Device' Attitude

Abstract: This paper describes the development of an all-in-one mobile learning platform, to support students' use of their own mobile handheld devices for assessment and feedback. The application incorporates several features that can be found in many other individual applications, into one platform. The features allow students' participation in peer feedback activities; they also enable students to access their feedback, leave comments on their summative feedback, participate in class discussions, take formative asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The findings also enabled the enunciation of the pedagogical and technical requirements for a mobile web application (Bikanga Ada 2013a, Bikanga Ada 2014a, 2014b, 2014c). Based on this, another aspect, ICT infrastructure , was added to the framework.…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…The findings also enabled the enunciation of the pedagogical and technical requirements for a mobile web application (Bikanga Ada 2013a, Bikanga Ada 2014a, 2014b, 2014c). Based on this, another aspect, ICT infrastructure , was added to the framework.…”
Section: Resultsmentioning
confidence: 86%
“…Based on the infrastructure requirements identified that led to the addition of the ICT infrastructure aspect, a mobile web application, MyFeedBack (Bikanga Ada 2013a, Bikanga Ada 2014a, 2014b, 2014c), was developed. As a result of MyFeedBack development and early trials (Bikanga Ada 2013b, p. 2495), the following dimensions were added to the framework:…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This paper presents the results of tracking students' engagement with their assessment feedback between 2013 and 2015 using a prototype mobile web application, MyFeedBack [1], [2]. It presents the digital footprinting results of three studies on student engagement with their feedback by answering the following questions: 'Do they collect it?'…”
Section: Introductionmentioning
confidence: 99%